Chinese Language Teaching and Learning in Kenya in the Prospects of China's Reform and Opening-up - Methody Florian Owaki; Mercy Mweni Kathina; Christopher Khayeka-Wandabwa; Francis Maina Gichuru; Eunice Amimo (ÜNİVERSİTEPARK Limited, 2019)
Teaching and learning of Chinese as a foreign language and its culture is complex for Kenyan learners. It requires them to consider contrasting intellectual, policy and economic dimensions that instead of aiding its propagation among Kenyan learners, could even facilitate a hindrance to its progression. Potential measures that could be embraced are examined in this study based on the current context in lieu of proper guidelines or policy for foreign language learning, and in the midst of China's reform and opening-up. The study adopts Stern's second language learning theoretical approach, documentary and discourse analysis as complementary to a preliminary exploratory survey. Chinese and Kenyan partnering institutions in higher education and its intersections through Chinese language development and cultural exchange are well-attuned towards attaining a competitive cadre of bilingually educated Kenyans who are appreciative of the cultural diversity between the two nations. This affords Chinese and Kenyan nationals the opportunity to engage with each other in efficient bidirectional exchanges for common intellectual and economic prosperity founded on various exchange agreements. In the quest for greater Chinese language and culture propagation, increased bidirectional participation of stakeholders in curriculum-related policymaking and implementation processes are sought. The mobilization of strategic resources through exchanges between China and Kenya hold the promise to a more certain cooperative future for all. Avenues on resource mobilization with a focus on efficient human resource management, together with an opportunities linkage framework, would benefit both countries, and thereby reinforce a common intellectual and economic prosperity